ART OF PAINT POURING : swipe, swirl & spin. - VanEver, Amanda (Fluid art series, 2020)
The Art of Paint Pouring: Swipe, Swirl & Spin builds on the basics of creating fluid art presented in The Art of Paint Pouring to take your skills to the next level.